(untitled) (Research, Society and Development, 2022)
In the current epidemiological scenario that Brazil is experiencing, with the outbreak of the new Coronavirus caused by the SARS-CoV-2 - Covid-19 virus, measures have been taken to maintain social distance and inhibit the increase in contagion and number of deaths. As a result, several essential activities were affected, requiring the adaptation of these services. Given this perspective, the present research sought to foster methodologies in the teaching of Chemistry to deaf students, using remote tools and instruments that provide an easy acquisition of concepts, such as the use of experiments and Digital Information and Communication Technologies (DICTs). Thus, the study was carried out at the Escola Estadual Cidadã Integrada Técnica lza de Almeida Ribeiro, located in the city of Conde-Paraíba, with the participation of three external teachers of Chemistry, the internal teacher of Chemistry, a deaf student and a LIBRAS interpreter. The methodology used was based on qualitative and participant approaches. For the development of activities, remote meetings were held via Google Meet. In this context, experimentation was carried out, aiming to bring the student closer to the science of Chemistry, since it is undeniable that through experiments students develop better skills and abilities. According to the satisfactory results, it was observed that the presence of experimental practice is necessary in the student’s daily life, as it is an essential characteristic of Chemistry teaching.